Foundations of athletic training prevention, assessment, and management - Anderson, Marcia K. (Wolters Kluwer Health, 2017)
"Comprehensive, and evidence-based, Foundations of Athletic Training, 6th Edition integrates basic medical concepts and related scientific information to help athletic trainers and students develop a strong foundation in athletic training best practices. Using a problem-solving approach to the prevention, recognition, assessment, management, and disposition of sports-related injuries and diseases, the text helps students learn to think like practitioners and is fully aligned with the BOC competencies. This 6th Edition has been updated throughout to reflect current best practices in the field and includes four new chapters, new and updated references, and a powerful suite of online learning resources that save instructors time and help students succeed."--Publisher's description